Compliant constant-force linear-motion mechanism. (December 2016) - Tolman, Kyler A.; Merriam, Ezekiel G.; Howell, Larry L.
Abstract: A fully compliant constant-force mechanism that uses an initially angled parallel-guiding mechanism is proposed. A pseudo-rigid-body model (PRBM) of the mechanism is developed and validated using both finite element models and experimental prototype testing. The PRBM is used as a preliminary design tool to identify parameters that result in a constant-force mechanism. An adjustable version of the mechanism is also proposed and is used to assess the range of validity of the PRBM and highlights how the system response can be varied by changing the flexible beams inclination. A finite element based optimization is used to create a modified version of the mechanism that incorporates beam-end rotation effects and offers greater performance. Potential applications for the mechanism are discussed and it is demonstrated as a component of a statically balanced system.